PENGARUH RASIO LIKUIDITAS, SOLVABILITAS, AKTIVITAS DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2014-2017 - Wahyu Putri Sartika, 14.05.52.0297; Susilowati, Yeye (Students' Journal of Accounting and Banking, 2019)
This study examines the effect of liquidity ratios, solvability, activity and profitability on stock prices. Each ratio is proxied by the current ratio, debt to equity ratio, total asset turnover, return on equity and earnings per share. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2017. The sample in this study used 204 data from 51 manufacturing companies listed on the Indonesia Stock Exchange for the 2014-2017 period. In this study using hypothesis testing. Based on multiple linear regression tests on the research that has been done shows that liquidity, solvability ratios and activities have no significant effect on stock prices. While the profitability ratio has a positive and significant effect on stock prices.